Diagnostic utility of cytopathology for the diagnosis of malignant thyroid nodules in a Peruvian hospital - Luna-Victorio, Laura (2024)
Objectives: To determine the diagnostic performance of fine needle aspiration biopsy (FNAB) for diagnosing malignant thyroid nodules. Methods: This is a retrospective study that assessed thyroid FNABs in Guillermo Almenara-Irigoyen National Hospital in Lima, Peru, during a three-year period. Cytopathologic diagnosis of biopsies was categorized using the Bethesda System, considering categories V and VI as malignant, and category II as benign. A single biopsy per patient was obtained, and results with the highest value in the Bethesda System were considered. All patients underwent thyroidectomy and histopathological results were characterized as malignant or benign. Results: One hundred and seventy-three patients were included in the study. Their cytopathology results were Bethesda II to VI. Cytological diagnosis showed that 47.4% of all patients were Bethesda VI. Nearly sixty percent (59.5%) of thyroid nodules were malignant in histopathology, and papillary carcinoma was the most frequent neoplasm. Diagnostic performance of FNAB was high when considering Bethesda V and VI as malignant, with 91.92% sensitivity, 71.67% specificity, 84.26 positive predictive value, 84.31% negative predictive value, and 84.28% precision. Positive verisimilitude rate was 3.39; but this significantly improved when only Bethesda VI was considered as malignant, with 90.7% sensitivity, 89.58% specificity, 90.3% precision, and 8.71 positive verisimilitude rate. Conclusion: FNAB showed good performance. This study proved to be quite useful in our healthcare facility for detecting errors and promote improvement, as well as a model for future research in different healthcare instances.